Consumer Perceived Risks Factors Towards Online Purchase Intention of Electronic Products in Malaysia - Mohamed Shafieek, Muhammad Shahrir; Mohamed Shafieek, Muhammad Shahrir; Ismail , Affero (International Journal of Psychosocial Rehabilitation, 2020)
Online purchase is the mainstream of consumers’ obtaining products and services that will satisfy their needs. It is essential to understand the ultimate motive behind the transaction made by consumers’ and it is also important for suppliers and retailers to target the right channel to reach out to their customers. Therefore, it is crucial to understand the factors influencing consumers’ perceived risks towards online purchase intention especially during the purchase decision process. Taking this into consideration, the paper at hand has been crafted with the ultimate objective of unveiling the risks that are affecting consumers when purchasing through online, particularly in purchasing electronic products. In order to do so, this study has greatly relied on the framework that has been derived from previous literatures. In addition to this study, all the data were collected through a self-administered questionnaire via e-survey from consumers’ residing in Malaysia. The findings show that there are factors have been identified through Exploratory Factor Analysis that have a significant effect towards online purchase intention which are performance risk, social risk, privacy risk, psychological risk, and financial risk. As a conclusion, marketers should create effective marketing strategies in engaging consumers to purchase via online rather than offline. Additionally, online marketers should be more concerned about these attributes to increase customers’ online purchase intention that will increase customer loyalty in the long run.